New Public Role of Professors and Approaches TO Commercialization of Intellectual Property in UK - Shatokha, V.I.; Velichko О.G.; Polushenko V.А. (Science and Innovation, 2024)
The professor’s role in commercialization of scientific knowledge has been analyzed by the example of UK. A system for support of cooperation between the professors and the corporations has been considered. The «knowledge transfer partnership » and «executive short projects» schemes used by the UK universities are described. The procedure for intellectual property commercialization at the Coventry University is considered.